Looking for the needle in a downsized haystack: Whole‐exome sequencing unravels genomic signals of climatic adaptation in Douglas‐fir (Pseudotsuga menziesii). Issue 12 (17th May 2021) - George, Jan‐Peter; Schueler, Silvio; Grabner, Michael; Karanitsch‐Ackerl, Sandra; Mayer, Konrad; Stierschneider, Michael; Weissenbacher, Lambert; van Loo, Marcela
Abstract: Conifers often occur along steep gradients of diverse climates throughout their natural ranges, which is expected to result in spatially varying selection to local climate conditions. However, signals of climatic adaptation can often be confounded, because unraveled clines covary with signals caused by neutral evolutionary processes such as gene flow and genetic drift. Consequently, our understanding of how selection and gene flow have shaped phenotypic and genotypic differentiation in trees is still limited. A 40‐year‐old common garden experiment comprising 16 Douglas‐fir ( Pseudotsuga menziesii ) provenances from a north‐to‐south gradient of approx. 1, 000 km was analyzed, and genomic information was obtained from exome capture, which resulted in an initial genomic dataset of >90, 000 single nucleotide polymorphisms. We used a restrictive and conservative filtering approach, which permitted us to include only SNPs and individuals in environmental association analysis (EAA) that were free of potentially confounding effects (LD, relatedness among trees, heterozygosity deficiency, and deviations from Hardy–Weinberg proportions). We used four conceptually different genome scan methods based on FST outlier detection and gene–environment association in order to disentangle truly adaptive SNPs from neutral SNPs. We found that a relatively small proportion of the exome showed a truly adaptive signal (0.01%–0.17%) when population substructuring and multiple testing was accounted for. Nevertheless, the unraveled SNP candidates showed significant relationships with climate at provenance origins, which strongly suggests that they have featured adaptation in Douglas‐fir along a climatic gradient. Two SNPs were independently found by three of the employed algorithms, and one of them is in close proximity to an annotated gene involved in circadian clock control and photoperiodism as was similarly found in Populus balsamifera . Synthesis . We conclude that despite neutral evolutionary processes, phenotypic and genomic signals of adaptation to climate are responsible for differentiation, which in particular explain disparity between the well‐known coastal and interior varieties of Douglas‐fir. Abstract : 16 provenances of Douglas‐fir were analyzed by using phenotypic and genomic data. Our data show strong signals of genomic adaptation to local climate conditions.